Evaluation of Frequency of Feeding Silkworms (Tubifex sp.) on the Survival Fish Larvae of Puntius denisonii - Mohammad Ali Fadilah Ali; Sumaryam; Didik Budiyato Didik Budiyato; Wisnaningsih (JURNAL MINA SAINS, 2025)
Puntius denisonii is a highly valuable ornamental fish that is in great demand in the international trade market. However, overexploitation and habitat degradation have led to a decline. Cultivation efforts with an optimal feeding strategy are necessary to enhance the Survival and growth of this species in a controlled environment. This study aims to analyze the effect of different feeding frequencies of Tubifex sp. worms on the growth and survival rate of P. denisonii larvae and determine the optimal feeding frequency and timing. This research was conducted from January 20 to 29, 2025, at Bogorian Aquatics Farm, Bogor City, using a completely randomized design (CRD) with three feeding frequency treatments: three times per day (A), four times per day (B), and five times per day (C), with nine replications for each treatment. The observed parameters included survival rate and water quality. Data were analyzed using ANOVA at a 95% confidence level, followed by the Least Significant Difference test. The results showed that feeding frequency significantly affected the growth and survival rate of P. denisonii larvae but did not significantly affect water quality. Parameters of dissolved oxygen (5.35-5.37 mgL⁻¹), temperature (27.30-27.41°C), and pH (7.97-8.00) remained stable across all treatments. The treatment with a feeding frequency of five times per day yielded the best results in enhancing larval growth and Survival compared to other treatments. Increasing feeding frequency in P. denisonii aquaculture can improve survival rates without adversely affecting water quality if the aeration system is properly managed.